Factores jurídico-económicos para incorporar la multipropiedad o el tiempo compartido en el ordenamiento jurídico peruano - Rojas Ulloa, Milushka Felícitas (2023)
The objetive of this article is present work aims to determine the most relevant economic legal factors that allow the incorporation of the timeshare or timeshare system into the Peruvian legal system, as new modalities of tourist and recreational housing arise located along the throughout the Peruvian territory, subject ton an internal rule that distorts its essence by equipping it with a new forma o co-ownership. To do this, we have resorted to specialized literature, statistics, survays and interviews, which allow us to locate ourselves at the strategic intermediate point that enables, on the one hand, the security demanded by investors, and on the other, the protection that consumers require when acquiring said systems, considering for both situations the necessary supervision of an agency. state, from the constitution of the system to its extinction.